Factors Associated with Cranial Nerve Injury after Radiotherapy for Large Brain Metastases - Fang Zhou (Hindawi Limited, 2021)
This paper mainly studied the correlation factors of cranial nerve injury after radiotherapy for large brain metastases by investigating the influencing factors and predictors of cranial nerve injury, which can provide a good reference and idea for radiotherapy. Through a large number of experiments, it is proved that the research idea proposed in this paper is reasonable and correct.